Political Labeling on Social Media: a Netnographic Study of “SDM Rendah” in Indonesia’s 2024 Presidential Election on X (Twitter) - Ruth Novarefie Putri Paath; Azzahra Qubais Suprapto; Hayunaji Hayunaji; Muhammad Edi Irfandianto (Eduvest - Journal of Universal Studies, 2024)
The 2024 presidential election campaign in Indonesia has produced various unique phenomena, including the emergence of the "Low Human Resources'' (SDM Rendah) label directed at the supporters of candidate pair 02 by the supporters of candidate pairs 01 and 03. The existence of this label has become a spotlight because it reflects the dynamics of politics and social interaction within the community. In conducting the netnographic research strategy in this study, the primary focus is on gaining a deep understanding of the underlying reasons for this labeling, as well as how it affects public perception and the overall political dynamics. The social media platform X was selected as the research subject due to its crucial role in facilitating communicative interaction, including the labeling process. It is expected that the results of this research can provide deeper insights into the phenomenon of labeling in the political realm on the X social media platform, as well as provide a better understanding for politicians and the public regarding the importance of using social media platforms wisely in the political context. This research also has significant academic implications in the field of communication science, particularly in the theory of Computer-Mediated Communication (CMC), which can contribute to a deeper understanding of the role of social media in contemporary politics. The practical implications cannot be overlooked either, especially in the efforts to raise awareness of the power and impact of social media platforms in the political context during the 2024 presidential campaign in Indonesia.